The Supply of Physicians Waivered to Prescribe Buprenorphine for Opioid Use Disorders in the United States: A State-Level Analysis - Knudsen, Hannah K. (J Stud Alcohol Drugs, 2015)
OBJECTIVE: The U.S. Food and Drug Administration’s approval of buprenorphine in 2002 expanded options for treating opioid use disorder (OUD). Physicians who intend to treat OUD patients with buprenorphine must seek a waiver to prescribe it, which may contribute to state-by-state variation in the supply of waivered physicians. METHOD: This study integrates data extracted from the U.S. Drug Enforcement Agency’s database of waivered physicians with state-level indicators of the macro environment, health-related resources, and treatment demand. RESULTS: In December 2013, the average state had 8.0 waivered physicians per 100,000 residents (SD = 5.2). Large regional differences between states in the Northeast relative to states in the Midwest, South, and West were observed. The percentage of residents covered by Medicaid as well as the population-adjusted availability of opioid treatment programs and substance use disorder treatment facilities were positively associated with buprenorphine physician supply. Buprenorphine physician supply was positively correlated with states’ rates of overdose deaths, suggesting that physicians may seek the waiver in response to the magnitude of the opioid problem in their state. CONCLUSIONS: States with greater health-related resources, particularly in terms of the supply of opioid treatment programs and substance use disorder treatment programs, had more waivered physicians in 2013. The finding regarding Medicaid coverage suggests that states implementing Medicaid expansion under health reform may experience additional growth in buprenorphine physician supply. However, large regional disparities in the supply of waivered physicians may impede access to care for many Americans with OUD.